2015
DOI: 10.1186/s12885-015-1855-z
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor - a therapeutic target in gallbladder cancer

Abstract: BackgroundPoor prognosis in gallbladder cancer is due to late presentation of the disease, lack of reliable biomarkers for early diagnosis and limited targeted therapies. Early diagnostic markers and novel therapeutic targets can significantly improve clinical management of gallbladder cancer.MethodsProteomic analysis of four gallbladder cancer cell lines based on the invasive property (non-invasive to highly invasive) was carried out using the isobaric tags for relative and absolute quantitation labeling-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 54 publications
(71 reference statements)
0
32
0
Order By: Relevance
“…[ 4 ] Recent studies showed that MIF is overexpressed in many solid cancers and is closely related in the tumor cell proliferation, angiogenesis and tumorigenesis. [ 3 , 5 , 6 ] Moreover, the overexpression of MIF has been associated to tumor progression, metastasis and unfavorable prognosis in gastric, hepatocellular, pancreatic, and lung cancers, and oral squamous cell carcinoma and metastatic melanoma. [ 3 , 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Recent studies showed that MIF is overexpressed in many solid cancers and is closely related in the tumor cell proliferation, angiogenesis and tumorigenesis. [ 3 , 5 , 6 ] Moreover, the overexpression of MIF has been associated to tumor progression, metastasis and unfavorable prognosis in gastric, hepatocellular, pancreatic, and lung cancers, and oral squamous cell carcinoma and metastatic melanoma. [ 3 , 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies imply that MIF could be closely involved in the cell proliferation, angiogenesis and tumorigenesis by activating the MAPK/PI3K/Akt pathways . MIF has been reported to be overexpressed in various cancers, including gastric, esophageal, colorectal, liver, pancreatic, ovarian, breast and prostate cancers . Furthermore, MIF overexpression has been found to be related to a poor prognosis in hepatocellular carcinoma, oral squamous cell carcinoma, metastatic melanoma and pancreatic ductal adenocarcinoma …”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11] MIF has been reported to be overexpressed in various cancers, including gastric, esophageal, colorectal, liver, pancreatic, ovarian, breast and prostate cancers. 12,13 Furthermore, MIF overexpression has been found to be related to a poor prognosis in hepatocellular carcinoma, oral squamous cell carcinoma, metastatic melanoma and pancreatic ductal adenocarcinoma. 14 However, the exact role of MIF is not clearly understood in SCC of the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical and clinical studies have demonstrated that MIF is overexpressed and may correlate with tumor aggressiveness in many different types of human cancers such as prostate , bladder, and kidney cancer [30], cervical cancer [20], ovarian cancer [44,45], breast cancer [29], gastric cancer [29], hepatocellular carcinoma [46], colon cancer [47,48], pancreatic cancer [49,50], gallbladder cancer [51], lung cancer [29,52], melanoma [31], head and neck cancer [29], acute myeloid leukemia [53,54], glioblastoma [15,55,56], and NB [57][58][59][60]. Moreover, elevated MIF expression is correlated with a worse patient overall survival in a large variety of cancers such as breast cancer [29], gastric cancer [29], hepatocellular carcinoma [61], pancreatic cancer [49,50], metastatic melanoma [31], head and neck cancer [29], esophageal squamous cell carcinoma [62], acute myeloid leukemia [53], glioblastoma [29,56], and NB [57].…”
Section: Mif and Cancermentioning
confidence: 99%